(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This research is significant to the supervision development of primary science teachers. It aimed 1) to study conditions and problems of teaching reflection of the primary science teachers; 2) to develop reflective teaching supervision model for primary science teaching; 3) to evaluate the model of teaching reflection; and 4) to apply and evaluate the reflective teaching supervision model for primary science teachers, which is divided into 4 phases, namely: Phase 1 studying the state, of problems, and needs for reflection in teaching of elementary school science teachers. A sample group was 468 teachers and educational personnel affiliated with Sakon Nakhon Primary Educational Service Area Office 2, academic year 2017, by simple random sampling. Phase 2 developing the supervision model of reflective teaching for primary science teachers by analyzing empirical data from the school with best practice and in-depth interviewing 7 experts. The target group was selected by purposive sampling with indicators. Phase 3 assessing the supervision model on appropriateness, feasibility and usefulness by 9 experts. And Phase 4 trial and evaluation of the supervision model with the target group selected from 3 schools by purposive sampling with indicators. Participants were teachers, supervisors and school administrators. Statistical data analysis was conducted to find Mean, Standard Deviation and content analysis. The findings revealed that 1) The supervision implementation reflected in teaching of the primary science teachers, in overall with all 5 aspects, was at a moderate level ( = 3.33). The need for the reflective supervision model of the primary science teachers was at a high level ( = 4.45). 2) The development and quality inspection of the model draft called "IPORE Model" is appropriate, feasible and useful. 3) The evaluation of the reflective teaching supervision model of primary science teachers was at the highest level (= 4.74) 4). The trial and evaluation of the reflective teaching supervision model of primary science teachers and a guidebook affected the teachers, supervisors and school administrators gain higher knowledge and understanding regarding the reflective teaching supervision model after the development with statistical significant at the level of .05, the competency of learning management was at the highest level (= 4.64). The supervisors’ competency was in the highest level (= 4.57), and satisfaction towards applying the reflective teaching supervision model of primary science teachers was also at the highest level (= 4.88)